Fertility and twinning in Canadian reindeer - Godkin, G. F. (Rangifer, 1986)
This study was carried out from 1976 to 1981 on the Mackenzie Delta reindeer herd with the co-operation of the owners, Canadian Reindeer Ltd., Tuktoyaktuk, Northwest Territories. The reproductive organs of 4050 female reindeer (Rangifer tarandus) were collected at slaughter. The pregnancy rates averaged 99.5% of the females examined. In the years 1978 and 1981, 24.7% (713) of the animals were carrying twins, as compared to a twinning rate of 0.4%) observed for the intervening years. Nineteen animals were not pregnant. Of these, 14 were emaciated with no gross pathology* of the reproductive tract. Five females had either a mummified fetus or uterine adhesions preventing a viable pregnancy. Estimated fawn survival rates from birth to June varied from 51.7 to 95.7%. Fawn survival from June to yearlings of June the next year varied from 51 to 86.4% as determined by count at roundup. Increment averaged 15.8% per year after a slaughter of 13.4% of the herd yearly.